Comparative Analysis of Cooperative Health Level Using the Camel Method - INDRIYANI, Ni Made Vita; PUTRA, I Wayan Gde Yogiswara Darma (PT Keberlanjutan Strategis Indonesia, 2024)
Cooperatives are a means for the community to carry out savings and loans or transaction processes to meet needs. Cooperative health assessment is an assessment to measure the level of health of cooperatives that carry out savings and loan business activities, both conventional and Sharia. The implementation of health level assessments for cooperatives must be carried out at least once a year in accordance with the Regulation of the Minister of Cooperatives and SMEs of the Republic of Indonesia Number 06/Per/Dep.6/IV/2016, concerning guidelines for assessing the health of savings and loan cooperatives and cooperative savings and loan units. The CAMEL analysis method aims to assess or measure the level of health of banking companies based on financial ratios that emphasize five aspects, namely capital, asset quality, management, income, and liquidity. CAMEL analysis is the aspect that most influences the financial condition of banks and cooperatives. Therefore, CAMEL analysis is a reference in assessing the stability of cooperatives.